CONCEPTUAL APPROACHES TO STATE REGULATION OF SUSTAINABLE DEVELOPMENT IN UKRAINE - Buryk Z.M. (Pressing Problems of Public Administration, 2017)
Theoretical and conceptual approaches of state regulation of sustainable development should be based on the development of economic, environmental and social spheres. Systematized strategic position to introduce the conceptual bases of state regulation of sustainable development, which regulate and govern the transition to sustainable development in Ukraine from the Independence period and outlined the problems of their implementation. The selected lines and are key principles (conditions) effective implementation of the Strategy for Sustainable Development “Ukraine – 2020”.